Online teaching and students’ perceived level of math anxiety during covid-19 pandemic - Alina-Elena Grecu (Revista de Știinţe Educaţiei, 2022)
This study explores how teachers’ perceptions of students’ math anxiety changed during online learning imposed by the Covid-19 pandemic. Using the focus group method of qualitative research for a group of selected math teachers, we have looked into the following questions: How was the students’ perceived level of math anxiety in online classes? What differences and what similarities have the teachers noticed in comparison with the face-to-face learning? The results of the study show that the phenomenon of math anxiety is decreasing and is becoming less significant than in face-toface education. Moreover, our research showed that the frame description of how teachers perceived the students’ math anxiety implies two different different processes: the students’ engagement in online learning (SEO) and the students’ digital competences (DC). It seems that students’ digital competences has a positive effect on learning mathematics, a fact that leads to students’experiencing less anxiety. Also, the phenomenon of math anxiety may be caused by the lack of students’ engagement in online learning. Students who don’t have digital skills, tend to avoid participating in online mathematics classes.